Late i.v. steroid treatment for severe COVID‐19‐induced acute respiratory distress syndrome: a case report. Issue 1 (23rd September 2020) - Kumakawa, Yasuaki; Hirano, Yohei; Sueyoshi, Koichiro; Ishihara, Tadashi; Kondo, Yutaka; Kawasaki, Takaaki; Takeuchi, Yuji; Nakamura, Yuki; Ishikawa, Kouhei; Watanabe, Yusuke; Saito, Wataru; Matsuda, Shigeru; et al.
Abstract : Background: The efficacy of steroid treatment for coronavirus disease (COVID‐19) is unknown. Case presentation: A 67‐year‐old man was transported to our hospital due to impaired consciousness and respiratory failure. After admission, tracheal aspirate of the patient was harvested, and it tested positive for severe acute respiratory syndrome coronavirus 2 nucleic acid. He required veno‐venous extracorporeal membrane oxygenation to sustain his oxygenation. However, his respiratory failure did not improve for 20 days. On day 20 of admission, we started to use i.v. steroid therapy. On day 23, lung opacity on the chest X‐ray cleared and the patient's oxygen saturation improved significantly. We successfully removed extracorporeal membrane oxygenation on day 27. Conclusion: Our case report encourages more future trials to evaluate the therapeutic use of i.v. steroid in severe COVID‐19‐induced acute respiratory distress syndrome. Abstract : We report a case of COVID‐19‐induced extracorporeal membrane oxygenation treated by late i.v. steroid administration. Our case suggests the value of prospective clinical trials for the evaluation of steroid use in severe COVID‐19‐induced extracorporeal membrane oxygenation.